Microsoft Excel Virtual Training Plan for the Administrative Staff of the University of Guayaquil. - Cueva Zambrano, Félix André; Calderón Santana, Robert Joao; Ulloa Castro, Jefferson Enrique (Conexiones UG, 2025)
The purpose of this training program is to analyze the relevance of creating and carrying out online courses through an LMS platform for administrative employees of the University of Guayaquil. Fundamental metrics and academic interests will be considered in order to establish goals and develop an effective model. This platform improves the teaching process, focusing attention on specific functions and needs. It represents a new form of technology-driven educational environment. Online training programs are highly appreciated for remote learning, allowing anyone to enroll, with a virtually unlimited level of participation. The advancement of the information society has introduced a new approach to scientific reasoning, underlining the growing relevance of continuous learning standards. The methodology of the training plan through an LMS platform has a positive effect on the current results and coincides with the characteristics of the proposed orientation plan. Educational materials continue to evolve, dominated by the use of tools and technologies such as videos and personalized learning environments for administrative staff. The latest scientific trends suggest that for any subject and in any type of learning environment (individual, remote or hybrid), it is essential to have online course resources through an LMS platform.